Measuring and preventing alcohol use and related harm among young people in Asian countries: a thematic review - Heng Jiang; Xiaojun Xiang; Wei Hao; Robin Room; Xiaojie Zhang; Xuyi Wang (BMC, 2018)
Abstract Background The paper reviews alcohol consumption patterns and alcohol-related social and health issues among 15-29-year old young people in Asian countries, and discusses strategies for preventing and controlling alcohol use and related harms. Methods We searched Google Scholar, PubMed, and Web of Science for reports, reviews and journal articles published in English between 1st Jan 1990 and 31st August 2016. Results Forty-one reports, reviews and journal papers were identified and included in the final review. The current drinking levels and prevalence among young people are markedly different between eight included Asian countries, ranging from 4.2% in Malaysia to 49.3% in China. In a majority of the selected Asian countries, over 15% of total deaths among young men and 6% among young women aged 15-29 years are attributable to alcohol use. Alcohol use among young people is associated with a number of harms, including stress, family violence, injuries, suicide, and sexual and other risky behaviours. Alcohol policies, such as controlling sales, social supply and marketing, setting up/raising a legal drinking age, adding health warning labels on alcohol containers, and developing a surveillance system to monitor drinking pattern and risky drinking behaviour, could be potential means to reduce harmful use of alcohol and related harm among young people in Asia. Conclusions The review reveals that drinking patterns and behaviours vary across eight selected Asian countries due to culture, policies and regional variations. The research evidence holds substantial policy implications for harm reduction on alcohol drinking among young people in Asian countries -- especially for China, which has almost no alcohol control policies at present.